Penerapan Pembelajaran Berbasis Masalah untuk Meningkatkan Ketrampilan Berpikir Kritis Siswa Kelas IX dalam Pelajaran Ekonomi [Problem-Based Learning Implementation to Increase Grade IX Students' Critical Thinking Skill in Learning Economics] - Asih Enggar Susanti; Selvi Ester Suwu (Polyglot, 2016)
This study aims to determine grade IX students’ response to the application of problem-based learning in economics and to determine the increase in students' critical thinking skills using the problem-based learning method. The design of this research is Class-Action Research (CAR), with the subjects being 31 grade IX students at a Christian junior high school in the city of Tangerang. The research instruments used in the application of problem-based learning are the students’ daily test scores, surveys, feedback from supervising teachers and fellow students, interviews with mentor teachers, and journal reflections. Analysis of the data used is descriptive analysis of the value of students' daily tests, observations of feedback from fellow students and their teachers, interviews, and students’ questionnaires. The results show that students' response to problem-based learning can improve critical thinking skills of students in learning economics. It could be seen from the increase in students' critical thinking skills in both students’ ability to ask questions, answer questions, and analyze and solve problems presented by the author.BAHASA INDONESIA ABSTRAK: Penelitian ini bertujuan untuk mengetahui respon siswa kelas IX terhadap penerapan pembelajaran berbasis masalah dalam pelajaran ekonomi, dan untuk mengetahui peningkatan ketrampilan berpikir kritis siswa melalui pembelajaran berbasis masalah. Desain penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK), dengan subjek penelitian adalah siswa kelas IX yang terdiri dari 31 siswa pada salah satu SMP Kristen di kota Tanggerang. Instrumen penelitian yang digunakan pada penerapan pembelajaran berbasis masalah adalah nilai ulangan harian siswa, angket, hasil observasi berupa umpan balik dari guru pembimbing dan rekan mahasiswa, hasil wawancara bersama dengan guru mentor, dan jurnal refleksi. Analisis data yang digunakan adalah analisis deskriptif, yaitu pada nilai ulangan harian siswa, hasil observasi, wawancara serta angket siswa. Hasil penelitian menunjukan bahwa respon siswa terhadap pembelajaran berbasis masalah adalah positif dan dapat meningkatkan kemampuan berpikir kritis para siswa dalam mempelajari ekonomi. Hal ini terlihat dari peningkatan kemampuan berpikir kritis siswa baik dalam kemampuan bertanya siswa, menjawab pertanyaan, menganalisis serta menyelesaikan permasalahan yang diajukan oleh penulis.